Effective Business Communication via AI: A New Era of Efficiency and Impact - Mikeladze, Nino; Dolidze, Tamari; Abesadze, Anna; Maguire, Josef (European Scientific Journal, ESJ, 2026)
The world of business is undergoing constant transformation, with communication at its core. In the context of rapid technological advancement and the rise of Artificial Intelligence (AI), business communication—globally conducted in English—has experienced significant changes, particularly since the COVID-19 pandemic. Digitalization and globalization have further reshaped international business interactions, introducing AI-driven tools and English as a Lingua Franca (ELF) as central components of contemporary communication practices. This paper explores the transformative impact of AI on business communication, focusing on its integration into English for Business (EB) and Business Communication (BC) practices in Georgia. The study examines both the advantages and limitations of AI tools and evaluates their effectiveness in enhancing clarity, efficiency, and cross-cultural interaction. A quantitative survey was conducted among EB and BC instructors and field practitioners in Georgia. The findings reveal that while AI significantly increases communication speed, accessibility, and linguistic accuracy, concerns remain regarding over-reliance, reduced critical thinking, and ethical implications. The results indicate a strong positive correlation between AI usage and perceived communication efficiency, alongside a clear demand for structured guidelines and training frameworks. The study contributes to understanding the evolving landscape of AI-mediated business communication and offers practical recommendations for its balanced and effective implementation in educational and professional contexts.